Review—Key Strategies to Increase the Rate Capacity of Cathode Materials for High Power Lithium-Ion Batteries. Issue 14 (5th November 2020) - An, Qi; Sun, Xiaohong; Guo, Jinze; Cai, Shu; Zheng, Chunming
Abstract : Realizing ultra-fast charge and discharge of lithium-ion batteries (LIBs) is one of the effective ways to promote the popularity of electric vehicles, solve energy and environmental problems. A lot of studies have shown that low conductivity and low lithium-ion diffusivity are the major limiting factors for the rate performance of cathode. However, there is no systematic review on the methods to improve the rate performance of cathode for LIBs. Hence this review ground-breakingly summarizes a series of key strategies and their electrochemical mechanisms to increase the rate capacity of cathode materials. The limiting factors for the development of LIBs fast charging are introduced. It analyzes the working mechanisms of the nanostructure and micro-nanostructures. The influences of carbon coating with different carbon sources are introduced and compared in detail. The specific mechanisms and research results of surface coating modification and doping strategies in LiFePO4, layered structure cathode, and spinel structure cathode are reviewed. Moreover, innovative approaches such as spinel-layered composites preparation, structural-gradient design, and photo-accelerated fast charging are also provided. Finally, some existing challenges and development directions in the future are discussed.